Association between Retinal Microvascular Changes and Severity of Coronary Heart Disease in Hypertensive Patients - Jamil, Abu Baqar Md; Iqbal, Khaled Mohammad; Hossain, Mohammad Ashraf; Rashid, Khandaker Harun or; Hossen, Md Tufazzal; Sarker, Alok Chandra; Hossain, Md Shahadat; Das, Mrinal Kanti; Ahsan, Syed Ali (University Heart Journal, 2022)
Background : The prevalence of coronary artery disease is increasing day by day. In many cases it is undiagnosed. Hypertension is one of the risk factors of coronary artery disease. Hypertension also causes some changes in retina which is easy to diagnose in clinical practice. So the aim of this study is to predict coronary artery disease by seeing hypertensive retinal changes. Methods: A total of 100 patients with hypertension presenting to the emergency department with ischemic chest pain who underwent coronary angiography were studied. Presence or absence of coronary artery disease was determined. Optic fundi were assessed for hypertensive retinopathy which were photographed. Results: Mean ± SD age of the study population was 56.23±10.76 years. There were 75 men (75%) and 25 women (25%). Prevalence of coronary artery disease and hypertensive retinopathy were 84% and 44% respectively. There was association between coronary artery disease and retinopathy (P< 0.017). Age (P= 0.019), smoking (P=0.011) and dyslipidaemia (0.039) were identified as risk factors for coronary artery disease. Conclusion: Important observations from this study are that hypertensive retinopathy has an association with coronary artery disease. Retinal change can be used in predicting coronary artery disease in patients with hypertension which can be used as screening tool for diagnosing coronary artery disease in resource poor settings. University Heart Journal 2022; 18(2): 93- 97